Faktor-Faktor yang Memengaruhi Minat Investor Berinvestasi Syariah - Nur Azikin; Abdul Hamid Habbe; Muhammad Achyar Ibrahim (Accounting Department, Faculty of Economics and Business, Universitas Hasanuddin, 2023)
This study aims to test and analyze investment knowledge, consideration of sharia securities, minimal investment capital and perceived ease of use on sharia investment interest through the Bibit application. The research data was obtained through an online questionnaire (primary) with a sample of 100 respondents. This study uses a quantitative approach with multiple linear regression analysis. This study also uses the classical assumption test and hypothesis testing in the form of T test and F test. The results show that investment knowledge, consideration of sharia effects and perceived ease of use affect on sharia investment interest, while minimal investment capital does not affect on sharia investment interest. Taken together, investment knowledge, consideration of sharia securities, minimal investment capital and perceived ease of use affect on sharia investment interest.